Demonstrasi Alat Peraga Matematika Pada Siswa/Siswi Sekolah Dasar Kiupukan - Ladja, Yosepha Patricia Wua; Naimnule, Maria; Bete, Hendrika; Siahaan, Meiva Marthaulina Lestari (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This article describes the results of community service activities targeting students of Kiupukan State Elementary School, with the goal of enabling teachers to utilize varied and engaging learning media, such as concrete materials, to enhance mathematics learning outcomes. The concrete media used were teaching aids in the form of number rulers and number cards on the topic of integers. The number line and number cards were chosen as an alternative to overcome the problem, because they can help students understand the addition and subtraction of integers. In addition, they can also concretize the addition and subtraction of integers, which are abstract concepts. This research method was implemented through several stages, namely the preparation stage, implementation, and evaluation of the activity. The results of this community service activity were an increase in students' understanding at SDN Nispukan from a score of 22 before the activity to 77.8 after the activity. While at SDK, Kiupukan went from a score of 22 to 60.4. This Community Service activity needs to be carried out further on other abstract mathematics topics, but still using teaching aids.